Renova shareholder group announces preliminary final result of mandatory offer. Issue 10 (October 2015) - Unknown
Abstract : Russia's Renova Group has announced the preliminary final result of the mandatory offer of its subsidiary Tiwel Holding Ag, acting in concert with Liwet Holding Ag, JSC Metkombank and Lamesa Holding Sa, for all publicly held registered shares of Sulzer Ag after expiry of the additional acceptance period on 2 October 2015.